The Existence of Kuntara Raja Niti Book in the Value System of Lampung Society in Pekon Marga Kaya - Isdiyanto, Ilham Yuli; Alwajdi, Muhammad Farid; Nur, Muhammad (Sosial Budaya, 2023)
The indigenous people of Lampung Pepadun in Pekon Marga Kaya have the principle of piil pesenggiri which is detailed as a customary law guideline as stated in the Book of Kuntara Raja Niti, but it needs to be further analyzed about its existence amid the many processes of cultural penetration and assimilation brought by migrants. This research uses a multidisciplinary approach by directing to socio-legal forms, therefore the process of obtaining data is carried out directly by interviews. As a result, the people of Lampung in Pekon Marga Kaya still adhere to the principle of piil pesenggiri and its derivatives that represent the contents of Kuntara Raja Niti. The existence of the Kuntara Raja Niti Book is known by the people of Lampung Marga Kaya, although not many people know its context. However, applying the pesenggiri piil is substantially like applying Kuntara Raja Niti as a way of life and behavior. Local governments must establish clear policies that protect the existence of indigenous peoples and their laws.